Corrosion resistance assessment of nickel-titanium endodontic files with and without heat treatment - Tatiana Dias Costa; Elison da Fonseca e Silva; Paula Liparini Caetano; Marcio José da Silva Campos; Leandro Marques Resende; André Guimarães Machado; Antônio Márcio Resende do Carmo (Restorative Dentistry & Endodontics, 2021)
ObjectivesThe aim of this study was to evaluate the corrosion resistance of heat-treated (Reciproc and WaveOne) and non-heat-treated (ProTaper and Mtwo) superelastic nickel-titanium endodontic files when immersed in a 5.25% sodium hypochlorite solution.Materials and MethodsAnodic polarization curves were obtained with potential sweeps that began at the open circuit potential or corrosion potential (Ecorr). The pitting potential (Epit) was identified on the anodic polarization curve as the potential at which a sudden increase in current was observed. The micromorphology of the 28 tested files was analyzed before and after the electrochemical assay using scanning electron microscope (SEM). The data were analyzed using 1-way analysis of variance with the post hoc Bonferroni test (for Ecorr) and the Student t-test for independent samples (for Epit).ResultsThe mean Ecorr values were 0.506 V for ProTaper, 0.348 V for Mtwo, 0.542 V for Reciproc, and 0.321 V for WaveOne files. Only WaveOne and Protaper files exhibited pitting corrosion, with Epit values of 0.879 V and 0.904 V, respectively. On the SEM images of the ProTaper and WaveOne files, cavities suggestive of pitting corrosion were detected.ConclusionsSigns of corrosion were observed in both heat-treated and non-heat-treated files. Of the evaluated files, WaveOne (a heat-treated file) and ProTaper (a non-heat-treated file) exhibited the lowest corrosion resistance.